Non‐invasive system delivering microwaves energy for unwanted fat reduction and submental skin tightening: Clinical evidence. (19th July 2022) - Salsi, Benedetta; Fusco, Irene
Abstract: Background: Cervicomental contour represents an important aesthetic problem. Aims: This research evaluates the safety and the efficacy of a new non‐invasive system delivering microwave energy for the treatment of submental skin laxity and fat. Methods: Forty‐eight subjects underwent submental treatment with the device at hand at Poliambulatorio San Michele, Reggio Emilia, Italy. The treatment was performed on the submental area starting from 1.5 cm below the lower border of the mandible up to the hyoid bone. Treatment consisted of 6 sessions of 10 min, with a 2‐week interval between each session. At the baseline and upon follow‐up 12 weeks from the last treatment, the following evaluations were performed: Photographic evaluation, Clinician‐Reported Submental Fat Rating Scale (CR‐SMFRS), Submental Skin Laxity Grade (SMSLG), Five‐Point Likert Scale Questionnaire (LSQ) for Skin Laxity, Patient‐Reported Submental Fat Rating Scale (PR‐SMFRS) and Numeric Rating Scale (NRS) for pain evaluation. Results: Mean submental fat and laxity scores evaluation significantly decrease respectively from 3.4 ± 0.5 and 3.7 ± 0.5 at baseline to 1.7 ± 0.6 and 2.4 ± 0.6 ( p  < 0.01) at 12‐week follow‐up after the last treatment. The treatment was well‐tolerated according to the NRS results. Out of the 47 participants (70.2%), 33 were very satisfied or satisfied. Most patients denied experiencing any discomfort during and after the treatment with the non‐invasive device delivering microwaves. The submental subcutaneous fat reduction, the improvement of submental skin tightening, and aesthetic results are confirmed also by photographic evaluation. No side effects were observed. Conclusions: Our results showed the potential microwaves role in the treatment of localized submental subcutaneous adiposities and skin laxity.